POTENTIAL TOXIC CYANOBACTERIA IN THREE LAKES OF JAKARTA-BOGOR AREA, INDONESIA - Prihantini, Nining Betawati; Widyawan, Arya; Rianto, Ronny; Ariyani, Yuni; Wardhana, Wishnu; Hendrayanti, Dian (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2008)
The research was aimed to understand the composition and dominancy of aquatic microalgae, and to know the potential toxicity of Cyanobacteria occuring in three lakes of Jakarta-Bogor area. The study was done in 2006. The sampling sites were Lake Sunter 2 (North Jakarta), Lake Babakan (South Jakarta), and Lake Lido (Bogor). The water samples were taken using plankton-net (20 tan mesh) with horizontal tow. The results showed that. the number of microalgal genera in Sunter 2, Babakan, and Lido were different, i.e. 10 genera, 40 genera, and 14 genera, respectively. Cyanobacteria were dominant in Sunter 2 (96%) and Babakan (90.01%). The dominant Cyanobacteria in Sunter 2 was Planktothrix agardhii (53.48%), whereas in Babakan was Chroococcus dispersus (68.52%). The second abundant Cyanobacteria in Sunter 2 was Arthrospira (42.54%). Planktothrix agardhii and Arthrospira are known to produce harmful toxin.